Motivation and achievement in learning French as a foreign language in Malaysia - Alpha Bodian (2017)
The teaching and learning of some of the most widely spoken foreign languages such as English, Japanese, Mandarin and French are given emphasis in many education systems throughout the world. Similarly in Malaysia, opportunities are provided for students to learn foreign languages especially at tertiary institutions. This paper presents a study that investigated Malaysian undergraduates’ motivation and achievement, as well as the relationship between the two variables in learning FFL. The study involved 213 undergraduates who took French as a foreign language (FFL) in a public university. The motivation data were collected using an adapted version of Gardner’s (1985) Attitude/Motivation Test Battery (AMTB) and students’ grades for the elective French course provided the achievement data. The results show that both integrative and instrumental motivation contribute towards the undergraduates’ decision to learn FFL but they are more motivated to learn for instrumental reasons compared to integrative reasons. The achievement results show that more than half of the student population obtained very good to good grades in the FFL assessment. However, the Pearson correlation test results show that there is no statistically significant correlation between the two types of motivation and achievement. The paper ends with discussion on some implications of the findings on the teaching and learning of French as a foreign language such as the need to expose the learners to the target language community.